A protein particle vaccine containing multiple malaria epitopes. - Gilbert, S; Plebanski, M; Harris, S; Allsopp, C; Thomas, R; Layton, G; Hill, A (1997)
Ty virus-like particles consist of a single protein species that can be produced in yeast. Recombinant Ty-VLPs carrying a string of up to 15 defined cytotoxic T lymphocyte (CTL) epitopes from Plasmodium species prime protective CTL responses in mice following a single administration without adjuvant. Effective processing of epitopes from the string was demonstrated in vitro and in vivo and was not affected by flanking sequences.